Technical and economic analysis of a CSP plant presenting a low freezing ternary mixture as storage and transfer fluid. (1st May 2020) - Delise, T.; Tizzoni, A.C.; Menale, C.; Telling, M.T.F.; Bubbico, R.; Crescenzi, T.; Corsaro, N.; Sau, S.; Licoccia, S.
Highlights: Low freezing mixture as heat transfer fluid and storage material for solar plants. Thermo-physical and stability investigation of a low freezing molten salt mixture. Solar parabolic plant sizing. Active direct storage system with a low freezing molten salt mixture. Techno-economic analysis according to the estimated electric energy cost per KWh. Abstract: The selection of a proper heat transfer (HTF) and storage (HSM) material is a key parameter in the design of a CSP system, especially in the employment of parabolic trough concentrating solar power plants (CSP). The use of nitrates as HTF, alternatively to thermal oils, can increase the CSP efficiency and several mixtures have been proposed at this aim. The most employed molten nitrate salt is the so called "solar salt" that presents several advantages but also a relative high liquidus temperature point of 238 °C. The use, either as HTF or HSM, of a low melting mixtures is currently considered a promising alternative to decrease the investment cost and improve the manageability of CSP plants. In this work, a low melting fluid was selected, composed of calcium, sodium and potassium nitrate, and proposed to be used both as HTF and HSM in a direct and active storage system. The electric LCOEs was calculated for a medium size (50 MWe) plant located at the Priolo Gargallo site (Sicily-Italy). In order to evaluate the obtained outcome, the identical procedure was carried out considering the same size and location, and the "solar salt" and a thermal oil as heat transfer fluids, with the former as storage medium. The comparison between the results show that there is a clear, although limited, economic benefit in using the ternary mixture.